IMPLEMENTING SUSTAINABILITY EDUCATION IN SECONDARY SCHOOL: A CASE STUDY IN CURRICULUM LEADERSHIP - McDonald, Elani (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Integrating education for sustainability in secondary schools is vital for creating a sustainable future, as it has a significant impact on students’ attitudes, behaviours, and decision-making. A study by Stevenson et al. (2016) argues that sustainability education can foster students’ environmental awareness and knowledge, as well as promote their willingness to engage in pro-environmental actions. It enhances critical thinking, problem-solving, and communication skills, all of which are essential for addressing complex sustainability challenges (Scott, 2018). However, implementing education for sustainability in secondary schools presents several challenges, such as a lack of teacher training, inadequate resources, and the pressure to prioritize standardized testing (Orr, 2018). This paper will explore the progress and challenges taken by a group of schools in Qatar to systematically develop education for sustainability standards (from the Cloud Institute) in all aspects of the written, taught and assessed curriculum in all schools. To support schools, the ADKAR change theory was used to help plan for and develop curriculum leadership with school leaders.